The courses of maternal and paternal depressive and anxiety symptoms during the prenatal period in the FinnBrain Birth Cohort study - Riikka Korja; Saara Nolvi; Eeva-Leena Kataja; Noora Scheinin; Niina Junttila; Henna Lahtinen; Suoma Saarni; Linnea Karlsson; Hasse Karlsson (PUBLIC LIBRARY SCIENCE, 2022)
Maternal prenatal symptoms of depression and anxiety have been suggested to impose differential effects on later offspring development, depending on their characteristics, such as timing, intensity and persistence. Paternal symptoms have been less investigated. While knowledge on these trajectory characteristics is essential for improved comprehension of prenatal stress, prospective studies including both expecting parents have been scarce. We aim at identifying and comparing the trajectories of prenatal depressive and anxiety symptoms in both parents in a pregnancy cohort design. The sample included 3202 mothers and 2076 fathers who were recruited to the FinnBrain Birth Cohort study (WWW.finnbrain.fi). Depressive symptoms were assessed using the Edinburgh Postnatal Depression Scale (EPDS) and general anxiety by the anxiety scale of the Symptom Checklist-90 (SCL-90) repeatedly at 14, 24, and 34 gestational weeks. Five differential depressive and four anxiety symptom trajectories were identified across pregnancy both in mothers and in fathers. The trajectories of consistently low depressive or anxiety symptoms were associated with higher educational level in both parents, and with nulliparity and non-smoking during pregnancy in mothers. Parents with consistently high or increasing levels of symptoms had more often prenatal SSRI medication. The congruences between elevated depressive and anxiety symptoms at any point in pregnancy, as well as parental trajectories within families were low. However, in this population-based sample, the self-reported symptom levels of both parents were generally very low. Variance in timing and persistence of parent-reported prenatal depressive and anxiety symptoms is potentially important, while symptom trajectories are very similar in mothers and fathers. These differential symptom trajectories and the significance of their correlates should be acknowledged when studying prenatal stress exposures and the related outcomes in children.